The new political economy of pharmaceuticals : production, innovation and TRIPS in the global south - Lofgren, Hans; Williams, Owain David; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2013)
Some two decades will shortly have passed since the WTO's Trade Related Aspects of Intellectual Property Rights agreement came into force in 1995. This volume is the first cross-country analysis of how TRIPS has affected the capacity of 11 major low or medium income countries to produce generic drugs.
Keywords: Political science; Political economy; International relations; Economic policy; Development economics; Social medicine; Economic development